A comprehensive analysis of Helicobacter pylori plasticity zones reveals that they are integrating conjugative elements with intermediate integration specificity - Fischer, Wolfgang (BMC Genomics, 2014)
BACKGROUND: The human gastric pathogen Helicobacter pylori is a paradigm for chronic bacterial infections. Its persistence in the stomach mucosa is facilitated by several mechanisms of immune evasion and immune modulation, but also by an unusual genetic variability which might account for the capability to adapt to changing environmental conditions during long-term colonization. This variability is reflected by the fact that almost each infected individual is colonized by a genetically unique strain. Strain-specific genes are dispersed throughout the genome, but clusters of genes organized as genomic islands may also collectively be present or absent. RESULTS: We have comparatively analysed such clusters, which are commonly termed plasticity zones, in a high number of H. pylori strains of varying geographical origin. We show that these regions contain fixed gene sets, rather than being true regions of genome plasticity, but two different types and several subtypes with partly diverging gene content can be distinguished. Their genetic diversity is incongruent with variations in the rest of the genome, suggesting that they are subject to horizontal gene transfer within H. pylori populations. We identified 40 distinct integration sites in 45 genome sequences, with a conserved heptanucleotide motif that seems to be the minimal requirement for integration. CONCLUSIONS: The significant number of possible integration sites, together with the requirement for a short conserved integration motif and the high level of gene conservation, indicates that these elements are best described as integrating conjugative elements (ICEs) with an intermediate integration site specificity.